(untitled) (Management Dynamics, 2024)
The aim of the study is to investigate the impact of employee motivation on retention in the restaurant business in Kathmandu Valley. The study employs a descriptive and causal-comparative research design, which is well-suited for exploring the challenges associated with high turnover rates and employee dissatisfaction in the restaurant business. The population for this study comprises 923 employees working in the restaurant business across Nepal, with a specific focus on 385 employees at The Burger House and Crunchy Fried Chicken. A purposive sampling technique is used to select participants from different job roles, including restaurant business agents, supervisors, and managers, ensuring a diverse and representative sample. Data collection involves Questionnaire sources, primarily through surveys conducted with the selected participants in the restaurant business. The study’s findings reveal significant relationships between employee motivations and various factors, including rewards, workload, career development opportunities, and work culture. Workload, while statistically significant, has a more modest effect on retention compared to the other variables. Additionally, the study emphasizes the importance of a positive work culture. Employees are more inclined to stay with an organization that promotes a supportive and inclusive work environment.